Characterization of the sonority associated to woodwinds instruments through spectral analysis - González, Yubiry; Prati, Ronaldo (Anais do Simpósio Brasileiro de Computação Musical (SBCM), 2019)
The sonority is one of the definitions widely used by musicians when trying to define the color or timbral balances associated with individual or groups of instruments , such as for ensembles or orchestras. This definition obeys to subjective musical parameters associated with "color balance", "sound amplitude", among others. In the field of musical acoustics, it is well known that the sounds coming from musical instruments depend on several acoustic physical parameters such as Intensity, Frequency, and the number of harmonics, as well as other aspects including, association with its manufacturing process, such as geometry and materials used for construction. This work presents, from a spectral analysis of the timbre with the use of Fast Fourier Transform (FFT), Spectral Power Density (DPE) and Spectrograms, the characterization of the subjective concept of "sonority", for some instruments of the Woodwind family: Piccolo flute, transverse flute, clarinet and oboe. It is concluded that the stage of sound evolution as the attack and sustenance, allow the establishment of harmonics whose powers are fundamental to define the timbric "color" associated with each instrument, as well as the number of harmonics allowed to establish parameters of "sound identity", useful for the generation of a coefficient extracted from the obtained spectral analysis, which allows to advance in the characterization of the Sonority. The generalization of the method is suggested for all families of musical instruments.